Daphnetin inhibits α-MSH-induced melanogenesis via PKA and ERK signaling pathways in B16F10 melanoma cells. Issue 5 (23rd March 2022) - Nam, Garam; An, Sung Kwan; Park, In-Chul; Bae, Seunghee; Lee, Jae Ho
ABSTRACT: Daphnetin is a dehydroxylated derivative of coumarin isolated from Daphne species. However, the effect of daphnetin on melanogenesis has not been elucidated. This study aims to investigate the inhibitory effect of daphnetin on melanogenesis in α-melanocyte stimulating hormone (α-MSH)-treated B16F10 cells and its potential mechanism. Melanin content analysis and cellular tyrosinase activity assay showed that daphnetin inhibited melanin biosynthesis in α-MSH-treated B16F10 cells. Immunoblotting and qRT-PCR also indicated that daphnetin suppressed the expression of microphthalmia-associated transcription factor, a mastering transcription factor of melanogenesis and its downstream melanogenic enzymes including tyrosinase and tyrosinase-related proteins. Moreover, daphnetin downregulated the phosphorylation of PKA, ERK, MSK1, and CREB. Additionally, daphnetin inhibited melanin synthesis in UVB-irradiated HaCaT conditioned medium system suggesting that daphnetin has potential as an antipigmentation activity in a physiological skin condition. Our data propose that daphnetin inhibits melanogenesis via modulating both the PKA/CREB and the ERK/MSK1/CREB pathways. Graphical Abstract: